A magnesium-lithium-based composite material with a core-shell configuration and a preparation method thereof
By forming the microstructure of the TiB2/α-Mg core-shell structure in the magnesium lithium-based composite material, the problem of low plasticity of magnesium lithium-based composite material under high particle content is solved, and a comprehensive improvement of strength, modulus and plasticity is achieved.
Patent Information
- Application Number
- CN202310011729.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-05
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-01-05
AI Technical Summary
The problem of low plasticity of magnesium lithium-based composites under high particle content limits its promotion and application in various fields.
Through three stages of TiB2/Al powder precast block preparation, gas protection smelting and heat treatment, a microstructure with a TiB2/α-Mg core-shell structure is formed, which improves the strength and modulus of the magnesium lithium-based composite material under high particle content, and improves its low plasticity problem.
The strength, elastic modulus and plasticity of magnesium lithium-based composite materials have been significantly improved, forming a material with good mechanical properties.
Smart Images

Figure CN116254444B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of metal-based composite materials and their preparation; it relates to a particle-reinforced magnesium-lithium-based composite material and its preparation method, and in particular to a micro-nano TiB2 particle-reinforced magnesium-lithium-based composite material with a core-shell configuration and its preparation method. Background Art
[0002] Lightweighting of structural materials has always been a hot topic in the field of materials research. As one of the lightest structural metal materials, magnesium-lithium alloy has a very low density (generally less than 1.6 g / cm 3 ), it also has high specific modulus, specific strength, good plasticity and excellent electromagnetic shielding effect. However, magnesium-lithium alloys still have some problems that limit their promotion and application in various fields, including low absolute strength and stiffness and aging softening. Therefore, how to improve the strength and modulus of magnesium-lithium alloys is particularly important. Conventional magnesium-lithium alloy strengthening methods mainly include alloying and heat treatment methods. Tang Song et al. disclosed "A high-strength and high-thermal stability ultra-light magnesium-lithium alloy and its preparation method" (Publication No. CN114231809A), using alloying element Ag as a strengthening element, while improving the strength and thermal stability of magnesium-lithium alloys. However, the elastic modulus of magnesium-lithium alloys is difficult to be effectively improved by alloying and heat treatment methods. The idea of composite materials is adopted, and a high modulus phase is added to the magnesium-lithium alloy matrix, which can effectively improve the problem of low elastic modulus of magnesium-lithium alloys.
[0003] Among the preparation methods of various metal-based composite materials, the stirring casting method is the technical route that is closest to the actual industrial production conditions, and has the characteristics of low cost and large-scale production. However, due to the high activity of magnesium-lithium alloys, the selection of magnesium-lithium-based composite materials is very limited. The use of carbon nanotubes will react with lithium, and the generated compounds will reduce the interface strength of the composite material. The elastic modulus of oxide particles such as Al2O3 is not high enough, and the elastic modulus of the composite material is not significantly improved. The use of TiB2 ceramic particles (elastic modulus of 550GPa) is expected to effectively improve the strength and elastic modulus of magnesium-lithium alloys. Wu Shusen et al. disclosed "A hybrid reinforced aluminum-based composite material and its preparation method" (publication number CN107460376A), in which a variety of nanoparticles, micron-level aluminum or aluminum alloy powders are mixed to prepare millimeter-level composite particles, which are then pressed into prefabricated intermediate alloy blocks and then added to aluminum or aluminum alloy melts, which significantly improves the various properties of metal-based composite materials. However, the amount of reinforcement particles added to the stirring casting magnesium-lithium-based composite material is generally not more than 10% by mass, and too high a reinforcement content will cause the plasticity of the magnesium-lithium alloy to decrease significantly. Therefore, it is very difficult to maintain a considerable plasticity for the composites prepared under high particle content conditions. It is necessary to develop new compositions and preparation methods based on the characteristics of magnesium-lithium dual-phase alloys, design a reasonable microstructure configuration, and achieve the improvement of the strength and modulus of magnesium-lithium based composites under high particle content conditions, while improving their low plasticity. Summary of the invention
[0004] In view of the problem of low plasticity of the high-particle content reinforced magnesium-lithium composite material reinforced by stirring casting, the purpose of the present invention is to provide a micron-sized TiB2 particle-reinforced magnesium-lithium composite material with a core-shell structure and a preparation method thereof. The present invention is through three stages of TiB2 / Al powder prefabricated block preparation, gas shielded smelting and heat treatment, especially the semi-solid treatment stage in gas shielded smelting. Before adding lithium, α-Mg is first heterogeneously nucleated on the TiB2 particles to form a semi-solid slurry with a TiB2 / α-Mg core-shell structure, and then after adding lithium and casting, a magnesium-lithium composite material with a TiB2 / α-Mg core-shell structure in the microstructure is obtained, so as to achieve the improvement of the strength and modulus of the stirring-cast magnesium-lithium composite material at a high particle content, and at the same time significantly improve the problem of low plasticity of the composite material.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] In a first aspect, the present invention relates to a magnesium-lithium-based composite material with a core-shell configuration, wherein the mass percentages of the components in the magnesium-lithium-based composite material are: Li 6-9%, Al 1-7%, Y 0.3-2.5%, Yb 0.1-2%, TiB2 particles 8-16%, and the remainder is Mg.
[0007] Preferably, the diameter of the TiB2 particles is 1 to 5 μm. According to the kinetic theory of heterogeneous nucleation, reinforcement particles with too small a particle size (submicron) are not conducive to the occurrence of heterogeneous nucleation, and thus are not conducive to the formation of core-shell configuration, while particles with too large a particle size (above 10 μm) will significantly reduce the plasticity of the composite material and easily cause stress concentration.
[0008] In a second aspect, the present invention relates to a method for preparing a micron TiB2 particle reinforced magnesium-lithium based composite material with a core-shell configuration, the method comprising three stages: TiB2 / Al powder prefabricated block preparation, gas shielded smelting, and heat treatment.
[0009] S1. Preparation of TiB2 / Al powder prefabricated block: TiB2 particles and Al powder are subjected to composite ball milling to obtain composite powder; the composite powder after ball milling is subjected to cold pressing to obtain a prefabricated block;
[0010] S2. Gas protection melting: Gas protection melting: firstly, Mg single substance, Al single substance, Mg-Yb master alloy and Mg-Y master alloy are melted in proportion under protective atmosphere, stirred after the metal is melted, and the prefabricated block is added to the melt above the liquidus temperature, and then mechanically stirred and ultrasonically treated at a temperature close to the liquidus temperature, and then the temperature is rapidly raised to 690-730°C and kept still, then cooled to a semi-solid range, and Li single substance is added and kept warm, and then cast into shape after mechanical stirring;
[0011] S3. Heat treatment: performing solution heat treatment on the obtained composite material.
[0012] Preferably, when the TiB2 particles and the Al powder are composite-ball-milled, the mass ratio thereof is 1:1 to 5:1.
[0013] Preferably, the cold pressing pressure of the composite powder of TiB2 particles and Al after ball milling is 15-30 MPa, the holding time is 15-20 min, and it is carried out at room temperature (15-30° C.).
[0014] Preferably, argon is passed through the smelting process for protection, the first mechanical stirring time is 0.5 to 2 hours, the stirring speed is 400 to 800 rpm, the mechanical stirring time before casting is 5 to 10 minutes, and the stirring speed is 200 to 500 rpm.
[0015] Preferably, the ultrasonic treatment time during the smelting process is 0.5 to 1 h, and the ultrasonic power is 500 to 1500 W.
[0016] Preferably, the temperature range for cooling to the semi-solid temperature interval is 550-590°C.
[0017] Preferably, the solution treatment temperature is 200-380° C. and the time is 2-8 hours.
[0018] The present invention realizes the dispersed distribution of micron-sized TiB2 particles in the magnesium-lithium alloy through the preparation of TiB2 / Al powder prefabricated blocks, gas-protected smelting and heat treatment, and forms a microstructure with a TiB2 / α-Mg core-shell configuration, thereby overcoming the difficult problem of low plasticity of TiB2 particle-reinforced magnesium-lithium-based composite materials at high particle content. The prepared micron-sized TiB2 particle-reinforced magnesium-lithium-based composite materials with a core-shell structure have good strength and elastic modulus, and effectively improve plasticity.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1) The micron-sized TiB2 particles used in the present invention are ceramic particles commonly used in industry, have extremely high elastic modulus (550GPa) and strength, have low lattice mismatch with the α-Mg phase, and are easy to become heterogeneous nucleation sites for the matrix alloy, thereby achieving grain refinement of the matrix alloy;
[0021] 2) In the micron-sized TiB2 particle-reinforced magnesium-lithium-based composite material with a core-shell structure involved in the present invention, the Al2Y formed in the matrix alloy can be used as a reinforcement to achieve a synergistic strengthening effect with TiB2. Moreover, the addition of Y causes a significant spheroidization effect on the α-Mg phase of the magnesium-lithium dual-phase alloy, which is more conducive to the formation of a uniform core-shell structure;
[0022] 3) In the micron-sized TiB2 particle-reinforced magnesium-lithium-based composite material with a core-shell structure involved in the present invention, the Yb element in the matrix alloy also has a significant effect on the grain refinement of the alloy, thereby further improving the strength and plasticity of the composite material;
[0023] 4) The process flow of the present invention is simple and has broad application prospects for magnesium-lithium based composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0025] Figure 1 Schematic diagram of the microstructure of the magnesium-lithium based composite material with core-shell structure of the present invention;
[0026] Figure 2 This is a metallographic diagram of the magnesium-lithium based composite material prepared by the present invention. DETAILED DESCRIPTION
[0027] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0028] Example 1
[0029] This embodiment relates to a magnesium-lithium-based composite material with a core-shell structure and a preparation method thereof, wherein the mass percentage of each component in the magnesium-lithium-based composite material is Li 8%, Al 3%, Yb 0.5%, Y 0.5%, TiB2 particles 8%, and the remainder is Mg. The diameter of the TiB2 particles is 1 μm.
[0030] This embodiment relates to a micron TiB2 particle reinforced magnesium-lithium based composite material with a core-shell configuration. The process includes three stages: TiB2 / Al powder prefabricated block preparation, gas protection smelting, and heat treatment:
[0031] Preparation of TiB2 / Al powder prefabricated block: TiB2 particles and Al powder are subjected to composite ball milling to obtain composite powder, the mass ratio of TiB2 particles to Al powder is 1:1, and the composite powder after ball milling is cold pressed (15MPa, holding pressure for 20min) to obtain a prefabricated block;
[0032] Gas protection smelting: firstly, Mg single substance, Al single substance, Mg-Yb master alloy and Mg-Y master alloy are melted in proportion under protective atmosphere, stirred after the metal is melted, and the prefabricated block is added to the melt above the liquidus temperature, and then mechanically stirred (stirring speed 700rpm, time 0.5h) and ultrasonically treated (power 1500W, time 1h) at a temperature close to the liquidus temperature, and then the temperature is rapidly raised to 690℃ and kept still, then cooled to 570℃, Li single substance is added and kept warm, mechanically stirred (stirring speed 200rpm, time 10min), and then cast into shape;
[0033] Heat treatment: The obtained composite material was subjected to solution heat treatment at 350°C for 4 h.
[0034] Figure 1 Schematic diagram of the microstructure of the magnesium-lithium based composite material with core-shell structure of the present invention, Figure 1 It can be seen that the microstructure of the composite material in the present invention is composed of several TiB2 / α-Mg core-shell structures distributed in β-Li. Figure 2The metallographic image of the magnesium-lithium based composite material prepared by the present invention. The black particles in the metallographic image of the magnesium-lithium based composite material are TiB2, surrounded by white α-Mg phase, and the dark gray phase in the matrix is β-Li phase. The microstructure is similar to Figure 1 Correspondingly, the density of the magnesium-lithium based composite material is 1.54 g / cm 3 , yield strength 295MPa, tensile strength 335MPa, elastic modulus 61GPa, elongation 12%. The test specimens and methods of tensile properties (yield strength, tensile strength and elongation) are based on the national standard GB / T228.1-2010, and the test specimens and methods of elastic modulus are based on the national standard GB / T22315-2008, the same below.
[0035] Example 2
[0036] This embodiment relates to a magnesium-lithium-based composite material with a core-shell structure and a preparation method thereof, wherein the mass percentage of each component in the magnesium-lithium-based composite material is Li 9%, Al 7%, Yb 1%, Y 1%, TiB2 particles 10%, and the remainder is Mg. The diameter of the TiB2 particles is 5 μm.
[0037] This embodiment relates to a micron TiB2 particle reinforced magnesium-lithium based composite material with a core-shell configuration. The process includes three stages: TiB2 / Al powder prefabricated block preparation, gas protection smelting, and heat treatment:
[0038] Preparation of TiB2 / Al powder prefabricated block: TiB2 particles and Al powder are subjected to composite ball milling to obtain composite powder, the mass ratio of TiB2 particles to Al powder is 1:1, and the composite powder after ball milling is cold pressed (15MPa, holding pressure for 20min) to obtain a prefabricated block;
[0039] Gas protection smelting: firstly, Mg single substance, Al single substance, Mg-Yb master alloy and Mg-Y master alloy are melted in proportion under protective atmosphere, stirred after the metal is melted, and the prefabricated block is added to the melt above the liquidus temperature, and then mechanically stirred (stirring speed 800rpm, time 0.5h) and ultrasonically treated (power 1000W, time 0.5h) at a temperature close to the liquidus temperature, and then the temperature is rapidly raised to 700℃ and kept still, then cooled to 590℃, Li single substance is added and kept warm, mechanically stirred (stirring speed 400rpm, time 5min) and then cast;
[0040] Heat treatment: The obtained composite material was subjected to solution heat treatment at 330°C for 5 h.
[0041] The density of the magnesium-lithium based composite material is 1.56 g / cm 3, yield strength is 305MPa, tensile strength is 341MPa, elastic modulus is 64GPa, and elongation is 9.4%.
[0042] Example 3
[0043] This embodiment relates to a magnesium-lithium-based composite material with a core-shell structure and a preparation method thereof, wherein the mass percentage of each component in the magnesium-lithium-based composite material is Li 6%, Al 5%, Yb 2%, Y 1.5%, TiB2 particles 20%, and the remainder is Mg. The diameter of the TiB2 particles is 1 μm.
[0044] This embodiment relates to a micron TiB2 particle reinforced magnesium-lithium based composite material with a core-shell configuration. The process includes three stages: TiB2 / Al powder prefabricated block preparation, gas protection smelting, and heat treatment:
[0045] Preparation of TiB2 / Al powder prefabricated block: TiB2 particles and Al powder are subjected to composite ball milling to obtain composite powder, the mass ratio of TiB2 particles to Al powder is 5:1, and the composite powder after ball milling is cold pressed (30MPa, holding pressure for 15min) to obtain a prefabricated block;
[0046] Gas protection smelting: firstly, Mg single substance, Al single substance, Mg-Yb master alloy and Mg-Y master alloy are melted in proportion under protective atmosphere, stirred after the metal is melted, and the prefabricated block is added to the melt above the liquidus temperature, and then mechanically stirred (stirring speed 400rpm, time 2h) and ultrasonically treated (power 500W, time 1h) at a temperature close to the liquidus temperature, and then the temperature is rapidly raised to 700℃ and kept still, then cooled to 560℃, Li single substance is added and kept warm, mechanically stirred (stirring speed 500rpm, time 6min) and then cast immediately;
[0047] Heat treatment: The obtained composite material was subjected to solution heat treatment at 380°C for 8 h.
[0048] The density of the magnesium-lithium based composite material is 1.60 g / cm 3 , yield strength is 335MPa, tensile strength is 368MPa, elastic modulus is 69GPa, and elongation is 5.6%.
[0049] Comparative Example 1
[0050] This comparative example relates to a magnesium-lithium based composite material with a core-shell configuration and a preparation method thereof, wherein the components of the composite material are the same as those of Example 1. The preparation method of the composite material is substantially the same as that of Example 1, except that the mass fraction of the matrix alloy Li is 4%.
[0051] The density of the magnesium-lithium based composite material is 1.66 g / cm 3 , yield strength is 305MPa, tensile strength is 323MPa, elastic modulus is 62GPa, and elongation is 1.6%.
[0052] The Li content of the matrix alloy is lower than the lithium content range window of the dual-phase magnesium-lithium alloy, resulting in the inability to generate a core-shell configuration and the absence of the highly plastic β-Li phase, leading to a significant decrease in elongation.
[0053] Comparative Example 2
[0054] This comparative example relates to a magnesium-lithium based composite material with a core-shell configuration and a preparation method thereof, wherein the components of the composite material are the same as those of Example 2. The preparation method of the composite material is substantially the same as that of Example 2, except that the mass fraction of the matrix alloy Li is 15%.
[0055] The density of the magnesium-lithium based composite material is 1.51 g / cm 3 , yield strength is 198MPa, tensile strength is 234MPa, elastic modulus is 58.5GPa, and elongation is 15%.
[0056] The Li content of the matrix alloy is higher than the lithium content range window of the dual-phase magnesium-lithium alloy. The matrix alloy is composed of a single-phase β-Li phase with a high elongation, but it leads to a significant decrease in the strength of the composite material.
[0057] Comparative Example 3
[0058] This comparative example relates to a magnesium-lithium based composite material with a core-shell configuration and a preparation method thereof, wherein the components of the composite material are the same as those of Example 3. The preparation method of the composite material is substantially the same as that of Example 3, except that no Y element is added to the matrix alloy.
[0059] The density of the magnesium-lithium based composite material is 1.61 g / cm 3 , yield strength is 301MPa, tensile strength is 326MPa, elastic modulus is 65GPa, and elongation is 2.3%.
[0060] No Y element is added to the matrix alloy, and the spheroidizing effect of the Y element is not reflected, resulting in the formation of needle-shaped α-Mg phase. Therefore, there is severe stress concentration in the core-shell structure and the plasticity is very low.
[0061] Comparative Example 4
[0062] This comparative example relates to a magnesium-lithium-based composite material with a core-shell configuration and a preparation method thereof, wherein the components of the composite material are the same as those of Example 3. The preparation method of the composite material is substantially the same as that of Example 3, except that the Yb element is not added to the matrix alloy.
[0063] The density of the magnesium-lithium based composite material is 1.60 g / cm 3 , yield strength is 261MPa, tensile strength is 289MPa, elastic modulus is 63.9GPa, and elongation is 3.3%.
[0064] Without adding Yb element into the matrix alloy, the grain refining effect of Yb element cannot be realized, resulting in the formation of coarse grains, so the strength and plasticity of the composite material are poor.
[0065] Comparative Example 5
[0066] This comparative example relates to a magnesium-lithium-based composite material with a core-shell configuration and a preparation method thereof, wherein the components of the composite material are the same as those of Example 2. The preparation method of the composite material is substantially the same as that of Example 2, except that the temperature of the solution treatment is 150°C.
[0067] The density of the magnesium-lithium based composite material is 1.55 g / cm 3 , yield strength is 220MPa, tensile strength is 246MPa, elastic modulus is 63GPa, and elongation is 9.9%.
[0068] The temperature of the solution treatment is too low, resulting in the failure of the solid solution strengthening effect in the magnesium-lithium alloy, which makes the strength of the magnesium-lithium based composite material relatively low.
[0069] Comparative Example 6
[0070] This comparative example relates to a magnesium-lithium-based composite material with a core-shell configuration and a preparation method thereof, wherein the components of the composite material are the same as those of Example 3. The preparation method of the composite material is substantially the same as that of Example 2, except that the temperature for cooling to a semi-solid state is 500°C.
[0071] The density of the magnesium-lithium based composite material is 1.85 g / cm 3 , yield strength is 190MPa, tensile strength is 202MPa, elastic modulus is 61GPa, and elongation is 0.6%.
[0072] During the smelting preparation process of the magnesium-lithium based composite material, the temperature for cooling and adding lithium is lower than the semi-solid temperature of the magnesium alloy, resulting in the alloy being completely solidified at this time, making it impossible to add lithium and having very poor plasticity.
[0073] Comparative Example 7
[0074] This comparative example relates to a magnesium-lithium-based composite material with a core-shell configuration and a preparation method thereof, wherein the components of the composite material are the same as those of Example 3. The preparation method of the composite material is substantially the same as that of Example 2, except that no semi-solid treatment is performed and lithium is directly added at 700°C.
[0075] The density of the magnesium-lithium based composite material is 1.56 g / cm 3 , yield strength is 253MPa, tensile strength is 278MPa, elastic modulus is 64.5GPa, and elongation is 4%.
[0076] The magnesium-lithium-based composite material is not semi-solid treated during the smelting preparation process, and the formed microstructure does not have a TiB2 / α-Mg core-shell structure and has poor mechanical properties.
[0077] The present invention has many specific application paths, and the above is only a preferred embodiment of the present invention. It should be pointed out that the above embodiments are only used to illustrate the present invention, and are not used to limit the protection scope of the present invention. For those of ordinary skill in the art, several improvements can be made without departing from the principle of the present invention, and these improvements should also be regarded as the protection scope of the present invention.
Claims
1. A magnesium-lithium-based composite material having a core-shell configuration, characterized in that: The mass percentage content of each component in the composite material is: Li 6-9%, Al 1-7%, Y 0.3-2.5%, Yb 0.1-2%, TiB2 particles 8-20%, and the balance is Mg; The magnesium-lithium based composite material is prepared by a method comprising the following steps: S1. Preparation of TiB2 / Al powder prefabricated block: TiB2 particles and Al powder are subjected to composite ball milling to obtain composite powder; the composite powder after ball milling is subjected to cold pressing to obtain a prefabricated block; S2, gas protection smelting: firstly, Mg single substance, Al single substance, Mg-Yb master alloy, and Mg-Y master alloy are melted in proportion under a protective atmosphere, and stirred after the metal is melted, and the prefabricated block is added to the melt above the liquidus temperature, and then mechanically stirred and ultrasonically treated at a temperature near the liquidus temperature, and then the temperature is rapidly raised to 690-730°C and then kept still, and then cooled to a semi-solid range, and Li single substance is added and kept warm, and then mechanically stirred and then cast into shape; S3, heat treatment: subjecting the composite material obtained in step S2 to solid solution heat treatment; the temperature of the solid solution treatment is 200-380° C., and the time is 2-8 hours.
2. The magnesium-lithium based composite material having a core-shell structure according to claim 1, characterized in that: The diameter of the TiB2 particles is 1 to 5 μm.
3. The magnesium-lithium based composite material with a core-shell structure according to claim 1, characterized in that: When TiB2 particles and Al powder are compositely ball-milled, the mass ratio thereof is 1:1 to 5:
1.
4. The magnesium-lithium based composite material having a core-shell structure according to claim 1, characterized in that: The cold pressing pressure of the composite powder of TiB2 particles and Al ball milling is 15-30MPa, the holding time is 15-20min, and the temperature is 15-30℃.
5. The magnesium-lithium based composite material having a core-shell structure according to claim 1, characterized in that: During the smelting process, argon gas is passed for protection. The first mechanical stirring time is 0.5 to 2 hours, and the stirring speed is 400-800 rpm. The mechanical stirring time before casting is 5 to 10 minutes, and the stirring speed is 200 to 500 rpm.
6. The magnesium-lithium based composite material with a core-shell structure according to claim 1, characterized in that: During the smelting process, the ultrasonic treatment time is 0.5 to 1 h, and the ultrasonic power is 500 to 1500 W.
7. The magnesium-lithium based composite material having a core-shell structure according to claim 1, characterized in that: The temperature range of the semi-solid zone is 550~590℃.
Citation Information
Patent Citations
Hybrid strengthened aluminum matrix composite and preparation method thereof
CN107460376A
High-strength and high-thermal-stability ultralight magnesium-lithium alloy and preparation method thereof
CN114231809A
Preparation method of magnesium-based composite material containing various in-situ enhancing particles of rare earth
CN101956118A
Preparation method of micro-nanometer TiB2 particle reinforced magnesium-lithium-based composite material
CN111304506A